Mechanism and Design Analysis of Articulated Ankle Foot Orthoses for Drop-Foot - Alam, M.; Choudhury, I.A.; Azuddin, M. (Hindawi Publishing Corporation, 2014)
Robotic technologies are being employed increasingly in the treatment of lower limb disabilities. Individuals suffering from stroke and other neurological disorders often experience inadequate dorsiflexion during swing phase of the gait cycle due to dorsiflexor muscle weakness. This type of pathological gait, mostly known as drop-foot gait, has two major complications, foot-slap during loading response and toe-drag during swing. Ankle foot orthotic (AFO) devices are mostly prescribed to resolve these complications. Existing AFOs are designed with or without articulated joint with various motion control elements like springs, dampers, four-bar mechanism, series elastic actuator, and so forth. This paper examines various AFO designs for drop-foot, discusses the mechanism, and identifies limitations and remaining design challenges. Along with two commercially available AFOs some designs possess promising prospective to be used as daily-wear device. However, the design and mechanism of AFO must ensure compactness, light weight, low noise, and high efficiency. These entailments present significant engineering challenges to develop a new design with wide consumer adoption.